Tác động của chánh niệm đến ý định sử dụng dịch vụ kết nối vận tải của khách hàng tại Việt Nam - Hoàng Đàm Lương , Thuý; Nguyễn Thu , Hà (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study explores the impact of mindfulness on customer’s intention to use online ride-hailing services in Vietnam through the mediating variables of perceived usefulness, perceived ease of use and subjective norm. The survey was conducted with 229 customers in Vietnam by using an online questionnaire via Google during the period of March–April 2022. The research results show that mindfulness have positive influences on the intention to use online ride-hailing services of the Vietnamese customers through two mediating variables, namely perceived usefulness and subjective norm. As consequence, the study suggests several managerial implications to encourage customers in Vietnamese market to use online ride-hailing services and several theoretical implications for future research on the same subject.